The Influence of Foreign Direct Investment and Inflation on Economic Growth in Indonesia For The 2013-2023 Period - Abdillah Nurul Bahri; Wahab Zaenuri; Ali Mutardho (Jurnal Ilmiah Al-Tsarwah, 2024)
This study aims to analyze the influence of Foreign Direct Investment (FDI) and inflation on economic growth in Indonesia in the period 2013-2023. Using a quantitative approach, this study applies multiple linear regression on secondary data from the Central Bureau of Statistics (BPS) and Bank Indonesia or other secondary sources, with independent variables of FDI and inflation and the dependent variable in the form of the annual Gross Domestic Product (GDP) growth rate. The results of the analysis show that FDI has an insignificant negative effect on economic growth, while inflation shows a positive but also insignificant effect. These results indicate that neither FDI nor inflation dominantly determine Indonesia's economic growth during the period, so additional factors may be needed to maximize economic growth through macroeconomic stability. This study is expected to contribute to economic policies related to FDI and inflation control in Indonesia.